Identification of novel ligands of WDR47, using yeast two-hybrid analysis - McGillewie, L. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Biomedical Sciences. Molecular Biology and Human Genetics. Medical Biochemistry))--University of Stellenbosch, 2009.